Rapid detection of alveolar echinococcosis in hepatic nodules of horses by recombinase polymerase amplification assay - Tatsuro Hifumi; Tetsuya Tanaka; Miho Sato; Kohei Akioka; Chiaki Fujimata; Noriaki Miyoshi (Veterinary and Animal Science, 2023)
Alveolar echinococcosis in slaughtered horses remains a public health issue. This study aimed to develop a Recombinase polymerase amplification (RPA) assay targeting the mitochondrial NADH dehydrogenase subunit 5 (Nad5) gene of Echinococcus multilocularis for the rapid detection of equine alveolar echinococcosis. Thirty-six hepatic solid nodules obtained from each horse (n = 36) were evaluated based on histopathological examination and Nad5-targeted PCR and then submitted to the RPA assay. The results of the developed RPA assay were 94.4% consistent with those of Nad5 PCR and Cohen's kappa coefficient value was 0.89 statistically, indicating high agreement. In addition, the RPA assay using the plasmid samples was one hundredfold more sensitive than PCR testing. Consequently, these results suggest that the performance of the RPA assay developed in this study is equal to that of conventional PCR testing.